Chlamydomonas axonemal dynein assembly locus ODA8 encodes a conserved flagellar protein needed for cytoplasmic maturation of outer dynein arm complexes. Issue 1 (7th February 2015) - Desai, Paurav B.; Freshour, Judy R.; Mitchell, David R.
<x xml:space="preserve">Abstract</x> The Chlamydomonas reinhardtii oda8 mutation blocks assembly of flagellar outer dynein arms (ODAs), and interacts genetically with ODA5 and ODA10, which encode axonemal proteins thought to aid dynein binding onto axonemal docking sites. We positionally cloned ODA8 and identified the gene product as the algal homolog of vertebrate LRRC56. Its flagellar localization depends on ODA5 and ODA10, consistent with genetic interaction studies, but phylogenomics suggests that LRRC56 homologs play a role in intraflagellar transport (IFT)‐dependent assembly of outer row dynein arms, not axonemal docking. ODA8 distribution between cytoplasm and flagella is similar to that of IFT proteins and about half of flagellar ODA8 is in the soluble matrix fraction. Dynein extracted in vitro from wild type axonemes will rebind efficiently to oda8 mutant axonemes, without re‐binding of ODA8, further supporting a role in dynein assembly or transport, not axonemal binding. Assays comparing preassembled ODA complexes from the cytoplasm of wild type and mutant strains show that dynein in oda8 mutant cytoplasm has not properly preassembled and cannot bind normally onto oda axonemes. We conclude that ODA8 plays an important role in formation and transport of mature dynein complexes during flagellar assembly. © 2014 The Authors. Cytoskeleton Published by Wiley Periodicals, Inc.